Australian children dietary intakes with a focus on dietary fats. Issue 11 (December 2014) - Meyer, Barbara J.
<x xml:space="preserve">Abstract</x> Australian children are consuming far too much salt and more saturated fat than the recommended intakes and this is largely due to consumption of processed foods like biscuits, cakes, pies, pizza, hamburgers, and potato chips/crisps. They consume very little in the way of vegetables and this is why magnesium and calcium intakes are low. Australian children also do not consume the beneficial omega‐3 fats which are primarily found in fish and seafood. To achieve the nutrients for optimal health Australian children should reduce their intakes of processed food and increase their intakes of wholesome foods including fish/seafood and vegetables.